Opinion expression via user comments on news websites: analysis through the perspective of the spiral of silence. Issue 3 (4th March 2018) - Soffer, Oren; Gordoni, Galit
ABSTRACT: User comments have become an essential part of news websites. In this article, we examine this mode of public expression via the theory of the spiral of silence. This is done while adopting alternative measures, with regard to three major issues on the Israeli agenda, and in comparison to expression in public, as in the traditional theory. Based on an Internet survey ( n = 712), the present study results support the relevancy of the spiral of silence to the online comment sphere. Perceived support for one's opinion by the majority was found to have a positive and significant effect on the willingness to express opinion in the online sphere. The explanatory role of fear of isolation was more significant in the online sphere than in face-to-face context.